Proceedings of the 3rd International Conference on Education, Science, and Technology (ICEST 2019) 2020
DOI: 10.2991/assehr.k.201027.039
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychoeducation to Reduce Homesickness in Islamic Boarding School Students’

Abstract: This study aims to explore the picture of homesickness in the first-year student of Islamic Boarding School Ummul Mukminin. The study was conducted using two approaches namely survey and quasi-experiment. Participants are new students aged 13-15 years old. Participants were divided into 2 (two) stages. The first stage is a stage of need analysis, in which researchers spread open questionnaires and are distributed to 300 students before intervention in the form of psychoeducation. In the second stage, the quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…The relationship between sleep quality and participants with normal glucose levels, on the other hand, is largely unknown (8). A crosssectional study done at the Ummul Mukminin Islamic Boarding School by Sulastri et al, in 2020 showed that interventions in the form of psychoeducation were proven to be able to reduce the longing felt (9). While research by Machmud et al states that there is a relationship between sleep quality and headaches in students at Islamic boarding schools, based on these data and the results of the researchers' initial observations, life in Islamic boarding schools is accompanied by busy activities, academic requirement, and longing felt that make students feel stress (10).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sleep quality and participants with normal glucose levels, on the other hand, is largely unknown (8). A crosssectional study done at the Ummul Mukminin Islamic Boarding School by Sulastri et al, in 2020 showed that interventions in the form of psychoeducation were proven to be able to reduce the longing felt (9). While research by Machmud et al states that there is a relationship between sleep quality and headaches in students at Islamic boarding schools, based on these data and the results of the researchers' initial observations, life in Islamic boarding schools is accompanied by busy activities, academic requirement, and longing felt that make students feel stress (10).…”
Section: Introductionmentioning
confidence: 99%